2006
DOI: 10.15394/jdfsl.2006.1008
|View full text |Cite
|
Sign up to set email alerts
|

The 2006 Analysis of Information Remaining on Disks Offered for Sale on the Second Hand Market

Abstract: The ever increasing use and reliance upon computers in both the public and private sector has led to enormous numbers of computers being disposed of at the end of their useful life within an organisation. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…The (Jones, 2006) This research should make general computer users and members of the public aware of the implications of careless disposal procedures. In the cases of the organisations disposing of their information, members of the public should enquire about the standards and procedures in place for the disposal, as the system could contain their information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (Jones, 2006) This research should make general computer users and members of the public aware of the implications of careless disposal procedures. In the cases of the organisations disposing of their information, members of the public should enquire about the standards and procedures in place for the disposal, as the system could contain their information.…”
Section: Discussionmentioning
confidence: 99%
“…While some may query this methodology, as the disks were essentially not computer evidence but discarded equipment, it was thought to be essential practice as it allowed all the research to be performed in a non-intrusive manner, therefore, it did not affect or change any of the original information obtained. It also was used as a precautionary step, as in the research performed in 2006 by BT, material found on two of the disks necessitated them being passed to the police for further information (Jones 2006). In this research, no material was considered necessary to be passed onto the Garda Síochána (Irish Police -law enforcement).…”
Section: The Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The research methodology used was the same as that used in the earlier research (Jones 2005(Jones , 2006, with each disk being forensically imaged using commercial software and then stored in secure storage areas. The analysis was undertaken on the forensic images of the original disks.…”
Section: The Researchmentioning
confidence: 99%
“…In the 2006 survey, the research of 2005 was repeated and expanded to include a number of additional countries. The report (Jones et al, 2006) on research conducted in the second annual survey revealed that for countries surveyed in both years there had been no significant changes from the prior year in the amount and sensitivity of information that could be recovered from the disk drives obtained from the second hand markets of those countries. Additionally, the results from the disk drives obtained from the second hand markets of countries that had not been included in the 2005 survey were broadly similar to the other countries that were included in both the 2006 and 2005 surveys.…”
mentioning
confidence: 99%